Inflammatory bowel disease and the gut microbiota. Issue 4 (21st November 2021) - Wu, Nan; Mah, Cassandra; Koentgen, Sabrina; Zhang, Leo; Grimm, Michael C.; El-Omar, Emad; Hold, Georgina L.
Abstract: Abstract : Inflammatory bowel disease (IBD) is a group of immune-mediated disorders characterised by a chronic, relapsing-remitting inflammation predominantly affecting the gastrointestinal tract. IBD is incurable, affecting people in their most productive years. IBD is historically seen as a disease of Westernised nations although in recent times other countries have seen an exponential rise in cases. Although the exact pathogenesis remains unclear, evidence suggests that microbiota changes play a critical role in IBD pathogenesis. Over the past two decades, IBD has become one of the most studied human conditions linked to the gut microbiota. However, deciphering the intricate link between the gut microbiota and therapeutic efficacy remains elusive. This review will summarise the current evidence relating to the gut microbiota and its involvement in IBD pathogenesis as well as the impact of IBD treatments including pharmaceutical-, nutraceutical- and microbial-focused regimens on the gut microbiota.